The Question of (Mis)interpreting the Qur’ān by Muslims (American Journal of Islam and Society, 2012)
Although the Qur’ān calls Muslims to make peace with their enemies(Qur’ān 8:61‒62), some early Qur’ān exegetes1 interpret that to be abrogatedby subsequent war verses (Qur’ān 9:5; Qur’ān 9:12‒13). This,according to a sound methodology, is a misinterpretation. So why is theQur’ān often taken out of context on many issues, and on peace and warinjunctions in particular? In other words, why does misunderstanding seemso pervasive among Muslims of different generations on different matters?This is certainly one of the most important questions in the context of intellectualdiscussion about the Qur’ān and Islam for at least two reasons:1. The consequences of this question effectively undermine all genuineefforts to both divorce Qur’ān or Islam from the misconducts ofsome Muslims on several fronts, and to convey its universallypositive messages.2. The implications of this question appear to lend some credence tothe claims and analyses of those who see the pervasive nature ofthis misunderstanding as truly representing Islam ‒ one that, in theireyes, has to be considered rather genuine. Here, their underlyingpresumption is that there is no “misunderstanding” of the Qur’ān,for the very fact of its pervasiveness means that it must be the truerepresentation.The following are some honest attempts to offer a much-needed explanationin the face of these two potent and critical observations, but notas a way to justify the problem. Although the pervasive nature of misunderstandingthe Qur’ān may be overplayed (one always finds dissentingvoices that tend to offer more logical and supported opinions ‒ in thiscase, al-Ṭabarī or Ibn al-ʻArabī, the Jurist), it is true that Muslims rarelyacknowledge it as a problem, hardly address it adequately, or even contemplateits negative implications for Islam. The misguided understanding ofthe verses of peace and war, for example, came about through a delicate interplayof at least three factors ‒ namely, interpretive methodology, culturalenvironment, and ideological pursuits ‒ each of which is analyzed below ...